2018
DOI: 10.1016/j.cortex.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Apparent motion perception in lower limb amputees with phantom sensations: “obstacle shunning” and “obstacle tolerance”

Abstract: Phantom limbs are the phenomenal persistence of postural and sensorimotor features of an amputated limb. Although immaterial, their characteristics can be modulated by the presence of physical matter. For instance, the phantom may disappear when its phenomenal space is invaded by objects ("obstacle shunning"). Alternatively, "obstacle tolerance" occurs when the phantom is not limited by the law of impenetrability and co-exists with physical objects. Here we examined the link between this under-investigated asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…As in previous studies (Saetta et al, 2018;Shiffrar & Freyd, 1990;Stevens et al, 2000), we found that fast SOAs biased LAMP towards the visually guided perception of physically impossible movements. Slow SOAs instead induced the perception of physically possible movements, which are, based on previous findings (Orgs et al, 2016;Stevens et al, 2000), sensorimotorically guided.…”
Section: Discussion Study Isupporting
confidence: 90%
See 4 more Smart Citations
“…As in previous studies (Saetta et al, 2018;Shiffrar & Freyd, 1990;Stevens et al, 2000), we found that fast SOAs biased LAMP towards the visually guided perception of physically impossible movements. Slow SOAs instead induced the perception of physically possible movements, which are, based on previous findings (Orgs et al, 2016;Stevens et al, 2000), sensorimotorically guided.…”
Section: Discussion Study Isupporting
confidence: 90%
“…According to the motor theory of LAMP, the perception of physically possible movements is grounded in the observer's sensorimotor representations acquired through motor experience (Funk et al, 2005;Orgs et al, 2016;Saetta et al, 2018;Stevens et al, 2000;Thornton, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations